UPAYA GURU FIKIH DALAM MENINGKATKAN KETAATAN PERIBADATAN SISWA MA TANBIHUL GHOFILIIN BAWANG BANJARNEGARA - Aziz, Mukhlis Abdul; Maryono, Maryono; Fuadi, Salis Irvan (Faidatuna, 2023)
In order to increase worship observance among students at MA Tanbihul Ghofilin Bawang Banjarnegara, fiqh teachers have struggled. This study seeks to understand these struggles by identifying the factors that support and hinder these efforts.In this study, we used the qualitative description approach. Data were gathered so that in-depth interviews, research observations, and documentation could be used. Although interactive analysis is a method of data analysis, data editing and presentation are different at the information gathering stage.The study's findings are as follows: 1) that fiqh teachers have made efforts and adopted strategies to increase student worship observance; and 2) supporting and inhibiting factors in doing so.